Construction of nomogram model for risk of venous thromboembolism after spine surgery based on thromboelastography and coagulation indices - He, Yongtao; Wang, Zhen; Zheng, Xiang; Zhang, Xunmeng; Guo, Lianjin (Frontiers in Medicine, 2024)
Objective To construct a nomogram model for the risk of venous thromboembolism after spinal surgery based on thromboelastography and coagulation indices and give relevant verification. Methods Two hundred seventy-seven patients who underwent spinal surgery for spinal fractures admitted to our hospital were selected as the research subjects. According to whether venous thromboembolism occurred after surgery, they were divided into an occurrence group (confirmed by ultrasound or venography) of 34 cases and an absence group of 243 cases. The related materials, thromboelastograms and coagulation related indicators of the two groups were compared. The influencing factors of venous thromboembolism after spinal surgery were analyzed by univariate and multivariate regression models. Based on the influencing factors, the Nomogram model of venous thromboembolism after spinal surgery was established and its effectiveness was verified. Results The proportion of patients whose age was ≥51 years old, the alpha Angle, the coagulation index (CI), the maximum thrombus amplitude (MA) and the levels of serum D-dimer (D–D), fibrinogen (FIB), fibrin degradation products (FDP), and thrombin-antithrombin complex (TAT) in the occurrence group were all significantly higher than those in the non-occurrence group. The clot formation time (K) and coagulation reaction time (R) were all lower than those in the non-occurrence group (P < 0.05). After Logistic multivariate analysis, alpha Angle, K, D-D, FDP, and TAT were all independent influencing factors of venous thromboembolism after spinal surgery (P < 0.05). Based on the independent influencing factors, the nomogram model of venous thromboembolism after spinal surgery was established, and the calibration curve was drawn. The consistency index was 0.838 (95% CI: 0.819–0.898), the goodness of fit test χ2 = 3.679, and P = 0.191 > 0.05. The calibration curve had a high degree of fit with the ideal curve. The clinical decision curve indicates that the net benefit of the prediction model is higher when the threshold probability is 0.1–0.9. Conclusion A nomogram model based on alpha Angle, K, D-D, FDP, TAT and other independent influencing factors of venous thromboembolism in patients after spinal surgery has a high degree of fitting and high prediction value.